2023
DOI: 10.3390/coatings13030650
|View full text |Cite
|
Sign up to set email alerts
|

Study on Thixotropic Properties of Asphalt Mastics Based on Energy Viewpoint

Abstract: An asphalt mastic has thixotropic characteristics that significantly influence its fatigue and healing performance. Therefore, understanding the thixotropy of an asphalt mastic is clearly of great importance. However, research in this area is still in the early stages. This study focuses on self-heating as one of the biasing performances of asphalt material by analyzing the viscosity, stress, and hysteresis loops the of asphalt mastics under cyclic shear loading. Twelve types of asphalt mastics fabricated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Due to the high percentage of mineral fillers, the effect of the thixotropy agent is reduced for formulations F1 to F7, and other filler-dominant effects are more pronounced. Moreover, the reduction of thixotropy in asphalt pavements was also shown in [25,26].…”
Section: Discussionmentioning
confidence: 86%
“…Due to the high percentage of mineral fillers, the effect of the thixotropy agent is reduced for formulations F1 to F7, and other filler-dominant effects are more pronounced. Moreover, the reduction of thixotropy in asphalt pavements was also shown in [25,26].…”
Section: Discussionmentioning
confidence: 86%
“…Its composition primarily consists of two components: asphaltene and maltene. Asphaltene, comprising 5%-25% of asphalt, is a high molecular weight compound with polar functional groups, such as carboxyl, alcohol, ketone, amine, and sulfur [13]. Maltene, on the other hand, has a relatively lower molecular weight and contributes to the workability of asphalt, being soluble in heptane [14].…”
Section: Introductionmentioning
confidence: 99%
“…Virginie et al used cone-plate thixotropy test equipment to carry out the time scanning and stress scanning of asphalt, took composite modulus as the evaluation index of thixotropy, and studied the influence of test temperature, loading rate, and loading duration on thixotropy [22]. By analyzing the viscosity, stress, and hysteretic curve of asphalt mastic under cyclic shear load, Ma et al found that adding fillers can significantly reduce the thixotropy, and different types of mineral fillers have little effect on the thixotropy [23]. Hassan et al studied the thixotropy of two adhesives containing different fillers, and the thixotropy model of asphalt can be established by DSR [24].…”
Section: Introductionmentioning
confidence: 99%